2017
DOI: 10.1186/s12906-016-1540-z
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic mixture improves fatty liver disease by virtue of its action on lipid profiles, leptin, and inflammatory biomarkers

Abstract: BackgroundA high fat diet has an essential role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). This condition is characterized by hepatic fat accumulation (steatosis) and is associated with obesity, diabetes, and fibrosis or cirrhosis of the liver. Probiotics may be useful in the treatment of steatosis. This study examined the effects of an ingested probiotic formulation on the lipid profiles, liver functions, leptin levels, and inflammatory marker levels of rats with NAFLD that had been ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 47 publications
2
54
0
Order By: Relevance
“…Another study also showed that cocktail of probiotics (L. acidophilus, L. plantarum, Bifidobacterium, and Bacillus subtilis strains) affected host adipose tissue hormone levels such as leptin, resistin, and hepatic function markers [31]. These results provide the validity of our results, suggesting that our results will contribute to discovering ameliorative action mechanisms of probiotics against NAFLD.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Another study also showed that cocktail of probiotics (L. acidophilus, L. plantarum, Bifidobacterium, and Bacillus subtilis strains) affected host adipose tissue hormone levels such as leptin, resistin, and hepatic function markers [31]. These results provide the validity of our results, suggesting that our results will contribute to discovering ameliorative action mechanisms of probiotics against NAFLD.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, treatment with two L. plantarum strains, K2 and K6, improved HF/HF diet-induced NAFLD in rats by regulating liver function, serum lipid levels, and lipogenesis via the AMPK pathway. Our literature investigation confirmed that several probiotics administered alone or in combination, have improvement effects on liver function in vivo [17,31]. L. plantarum NCU116, isolated from pickled vegetables, has indicated the effect amelioration of NAFLD by lowering the cholesterol property [17].…”
Section: Discussionsupporting
confidence: 71%
“…A meta-analysis conducted by literature review showed that multiple-strain probiotics are more effective than a single strain in reducing NEC (necrotizing enterocolitis) and mortality in infants [30]. Probiotics mixture, which contains five strains, was effective in the treatment of NAFLD by ameliorating increased lipid profiles, liver function, and inflammatory markers [31]. …”
Section: Discussionmentioning
confidence: 99%
“…In work reported in January 2017, Kamal Adel Amin and Hessah Mohammed Almuzafar at Imam Abdulrahman Bin Faisal University in Saudi Arabia examined the effect of adding probiotic bacteria to the diet of rats 4 . The supplement prevented rats on a high-fat, high-sucrose diet from developing NAFLD, which would have occurred on the same diet without the bacteria.…”
Section: Cause and Correctionmentioning
confidence: 99%